Efficacy and safety of belimumab therapy for patients with lupus nephritis: A meta‐analysis and a propensity score‐matched case–control study - Kai Zhang; Tiening Qi; Donghua Guo; Youxia Liu (Immunity, Inflammation and Disease)
Abstract Objective In this study, we performed a meta‐analysis and a propensity score‐matched case–control study to evaluate the efficacy and safety of belimumab in patients with lupus nephritis (LN). Methods We analyzed the data from three randomized controlled trials (RCTs) to assess the effects of belimumab treatment on renal improvement and adverse effects. Our study included a total of six LN patients who received belimumab treatment and an additional six LN patients who received standard therapy. All participants were followed up for a duration exceeding 96 weeks to evaluate the outcomes of the treatments. Results Our meta‐analysis incorporated data from three articles involving a total of 666 patients. The results of the analysis revealed that a higher proportion of patients who received belimumab treatment experienced renal improvement compared to those in the control group. The patients in belimumab group had a higher renal complete response rate and proteinuria improvement rate compared to the control group. However, belimumab treatment did not increase the renal partial response rate compared to the control group. The belimumab group also exhibited a higher proportion of patients who achieved normalization of antidouble‐stranded DNA, as well as normalization of low C3 and C4 levels. In our case–control study, significant improvement in proteinuria was demonstrated with belimumab at Week 48 (p = 0.037) and at all subsequent time points (all p < 0.05). Over the course of 96 weeks, belimumab treatment was associated with renal function stabilization and an increase in C3 and C4 levels. Moreover, the use of belimumab resulted in a reduction in glucocorticoid dosage at Week 24 (p = 0.02). Additionally, patients receiving belimumab treatment had a lower risk of severe treatment‐emergent adverse events, and no other significant adverse effects were observed between the two groups. Conclusions In patients with LN, the utilization of belimumab therapy has demonstrated notable improvements in renal response rates. Additionally, it has shown a decreased likelihood of serious treatment‐related adverse events and a diminished need for glucocorticoid dosage when compared to the active control group.